PRAGMATIC APPROACH OF WILLIAM JAMES AND SEON MASTER DAEHAENG TOWARDS RELIGION AND SCIENCE - Kim, Chae Young (Journal of Dharma, 2019)
This essay draws a parallel between William James, a scientific philosopher, and Seon Master Daehaeng, a religious leader in order to establish a thought involving the science of psychology within a religious context of human experiences, to help us achieve a better understanding of the world, and move forward towards a knowledge-oriented society. A fundamental compatibility towards knowledge societies would seem to be possible if we can determine how determinations of meaning in one discipline or perspective is found not to be in conflict with the determinations that belong to another point of view. Both, in some way, exist together. Having these two points as the base of this research, I am examining the perspectives of William James and Daehaeng to form a synthesis that would help human society to move towards societies that are guided by knowledge.